Biodielectrics: old wine in a new bottle? - Barnana, Hema Dinesh; Tofail, Syed A. M.; Roy, Krittish; O’Mahony, Charlie; Hidaši Turiničová, Veronika; Gregor, Maroš; ul Haq, Ehtsham (Frontiers in Bioengineering and Biotechnology, 2024)
Biodielectrics is a subset of biological and/or bioinspired materials that has brought a huge transformation in the advancement of medical science, such as localized drug delivery in cancer therapeutics, health monitoring, bone and nerve repair, tissue engineering and use in other nanoelectromechanical systems (NEMS). While biodielectrics has long been used in the field of electrical insulation for over a century, polar dielectric properties of biological building blocks have not been well understood at the fundamental building block level. In this review article, we provide a brief overview of dielectric properties of biological building blocks and its hierarchical organisations to include polar dielectric properties such as piezo, pyro, and ferroelectricity. This review article also discusses recent trends, scope, and potential applications of these dielectrics in science and technology. We highlight electromechanical properties embedded in rationally designed organic assemblies, and the challenges and opportunities inherent in mapping from molecular amino acid building blocks to macroscopic analogs of biological fibers and tissues, in pursuit of sustainable materials for next-generation technologies.